Impact of Aging on the Frequency, Phenotype, and Function of CD161-Expressing T Cells - van der Geest, Kornelis S. M.; Kroesen, Bart-Jan; Horst, Gerda; Abdulahad, Wayel H.; Brouwer, Elisabeth; Boots, Annemieke M. H. (Frontiers in Immunology, 2018)
Immune-aging is associated with perturbed immune responses in the elderly. CD161-expressing T cells, i.e., the previously described subsets of CD161+ CD4+ T cells, CD161high CD8+ T cells, and CD161int CD8+ T cells, are highly functional, pro-inflammatory T cells. These CD161-expressing T cells are critical in immunity against microbes, while possibly contributing to autoimmune diseases. So far, little is known about the impact of aging on the frequency, phenotype, and function of these CD161-expressing T cells. In the current study, we investigated the impact of aging on CD161+ CD4+ T cells, CD161high CD8+ T cells, and CD161int CD8+ T cells in peripheral blood samples of 96 healthy subjects (age 20–84). Frequencies of CD161+ CD4+ T cells and CD161int CD8+ T cells were stable with aging, whereas frequencies of CD161high CD8+ T cells declined. Although CD161high CD8+ T cells were mostly T cell receptor-Vα7.2+ mucosal-associated invariant T cells, CD161 expressing CD4+ and CD8+ T cells showed a limited expression of markers for gamma–delta T cells or invariant natural killer (NK) T cells, in both young and old subjects. In essence, CD161-expressing T cells showed a similar memory phenotype in young and old subjects. The expression of the inhibitory NK receptor KLRG1 was decreased on CD161+ CD4+ T cells of old subjects, whereas the expression of other NK receptors by CD161-expressing T cells was unaltered with age. The expression of cytotoxic effector molecules was similar in CD161high and CD161int CD8+ T cells of young and old subjects. The ability to produce pro-inflammatory cytokines was preserved in CD161high and CD161int CD8+ T cells of old subjects. However, the percentages of IFN-γ+ and interleukin-17+ cells were significantly lower in CD161+ CD4+ T cells of old individuals than those of young individuals. In addition, aging was associated with a decrease of nonclassic T helper 1 cells, as indicated by decreased percentages of CD161-expressing cells within the IFN-γ+ CD4+ T cell compartment of old subjects. Taken together, aging is associated with a numerical decline of circulating CD161high CD8+ T cells, as well as a decreased production of pro-inflammatory cytokines by CD161+ CD4+ T cells. These aging-associated changes could contribute to perturbed immunity in the elderly.